Maternal polymorphic loci of rs1979277 serine hydroxymethyl transferase and rs1805087 5-methylenetetrahydrofolate are correlated with the development of fetal growth restriction: A case-control study - Olesya Efremova; Irina Ponomarenko; Mikhail Churnosov (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Key reactions in folate-mediated single-carbon metabolism are regulated by folate cycle enzymes. Violations of the folate cycle may be associated with the occurrence of fetal growth restriction (FGR) in pregnant women. Objective: To study the relationship between polymorphisms of folate cycle genes in the mother with the development of FGR. Materials and Methods: In this case-control study, 122 pregnant women with FGR and 243 pregnant women with normal newborn weight were enrolled. The polymorphic loci of folate cycle genes including rs1805087 5-methylenetetrahydrofolate (MTR) and rs1979277 serine hydroxymethyl transferase (SHMT1) were examined. The study of polymorphisms was carried out through the TaqMan probe detection method using polymerase chain reaction. Logistic regression was used to analyze the associations of the polymorphisms. Results: It was established that the T allele rs1979277 of the SHMT1 gene was correlated with the development of FGR within the framework of the allelic (OR = 1.67, 95% CI 1.20-2.33, p perm < 0.01), additive (OR = 1.69, 95% CI 1.20-2.37, p perm < 0.01), dominant (OR = 1.81, 95% CI 1.15-2.87, p perm = 0.01) and recessive (OR = 2.34, 95% CI 1.15-4.73, p perm = 0.01) models. The association of the G rs1805087 allele of the MTR gene with the occurrence of FGR was also identified following the recessive model (OR = 3.01, 95% CI 1.05-8.68, p perm = 0.04). Conclusion: Our results indicated that maternal polymorphic loci rs1979277 SHMT1 and rs1805087 MTR may be associated with the development of FGR.